2021
DOI: 10.3389/fpls.2021.634393
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic Signaling and Senescence, an Ancient Solution to a Modern Problem?

Abstract: The length of the day (photoperiod) is a robust seasonal signal originated by earth orbital and translational movements, a resilient external cue to the global climate change, and a predictable hint to initiate or complete different developmental programs. In eukaryotic algae, the gene expression network that controls the cellular response to photoperiod also regulates other basic physiological functions such as starch synthesis or redox homeostasis. Land plants, evolving in a novel and demanding environment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 166 publications
(229 reference statements)
1
13
0
1
Order By: Relevance
“…In previous studies, CO was identified as being differentially expressed in the shoot apical meristem during the early stages of floral differentiation, and although CO was upregulated, FT, its main target, was not (Wellmer et al, 2006;Chen et al, 2018). This hinted to a possible different role of CO compared with that described in induction of flowering by photoperiod (Sua ´rez-Lo ´pez et al, 2001;Serrano-Bueno et al, 2021). Here we describe the presence of CO protein in floral organs with a novel pattern of expression and a role in flower senescence.…”
Section: Discussionmentioning
confidence: 65%
“…In previous studies, CO was identified as being differentially expressed in the shoot apical meristem during the early stages of floral differentiation, and although CO was upregulated, FT, its main target, was not (Wellmer et al, 2006;Chen et al, 2018). This hinted to a possible different role of CO compared with that described in induction of flowering by photoperiod (Sua ´rez-Lo ´pez et al, 2001;Serrano-Bueno et al, 2021). Here we describe the presence of CO protein in floral organs with a novel pattern of expression and a role in flower senescence.…”
Section: Discussionmentioning
confidence: 65%
“…The perception of and response to photoperiods in plants require a sensing mechanism, which involves the detection of light (via photoreceptors or chloroplasts) and the measurement of time (via the circadian clock) ( Jackson, 2009 ; Serrano-Bueno et al, 2021 ).…”
Section: Molecular Mechanisms Involved In the Perception Of Light And The Photoperiodmentioning
confidence: 99%
“…The synchronization of the correct timing of protein stabilization during long days with the circadian-regulated expression of FKF1 , GI , and CDF1 is essential for photoperiodic responses, such as flowering. Interesting to mention is that the CO-FT-GI-CDF hub is conserved among distantly related flowering plants ( Serrano-Bueno et al, 2021 ).…”
Section: Molecular Mechanisms Involved In the Perception Of Light And The Photoperiodmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoperiod, or daylength, is a robust seasonal cue that is measured by organisms ranging from algae (Serrano-Bueno et al, 2021) and fungi (Roenneberg and Merrow, 2001), to higher plants (Thomas and Vince-Prue, 1996) and vertebrates (Gwinner, 2003). This circannual signal allows the anticipation of environmental changes and thus the coordination of long-term developmental and reproductive processes, such as tuberization in potatoes (Osnato et al, 2021) and maturation of animal gonads (Nakane and Yoshimura, 2019).…”
Section: Introductionmentioning
confidence: 99%